Population Pharmacokinetic and Pharmacodynamic Modeling Analysis of GCC‐4401C, a Novel Direct Factor Xa Inhibitor, in Healthy Volunteers. (11th August 2016) - Choi, HY; Choi, S; Kim, YH; Lim, HS
Abstract : GCC‐4401C, an orally active direct factor Xa inhibitor that is similar to rivaroxaban, is currently under development for venous thromboembolic disease (VTE). The purpose of this study was to characterize the pharmacokinetics (PKs) and pharmacodynamics (PDs) of GCC‐4401C by population modeling analysis and to predict proper dosage regimens compared to rivaroxaban using data from two phase I clinical studies. Plasma GCC‐4401C concentrations over time were best described by a two‐compartment linear model and body weight was associated with central volume of distribution. Relevant PD markers generally changed in a dose‐dependent manner and were described well with sigmoid, simple maximum effect, or linear models. GCC‐4401C was absorbed more rapidly than rivaroxaban. Comparisons based on simulations of PD marker changes over time suggest that 20 mg and 40 mg of GCC‐4401C administered under fasted status are comparable to 10 mg and 20 mg of rivaroxaban under fed status.